2013
DOI: 10.1259/dmfr.20120199
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular joint (TMJ) disc position in patients with TMJ pain assessed by coronal MRI

Abstract: Objectives: To assess the position of the temporomandibular joint (TMJ) disc in patients with TMJ pain and compare it with equivalent published data of asymptomatic volunteers. Methods: The oblique coronal closed-and open-jaw MR images from 66 patients with TMJ pain were evaluated. Clinical examination followed the research diagnostic criteria for temporomandibular disorders. In all coronal images, the transverse condylar axis and the medial and lateral edges of the disc were determined using special software.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 32 publications
3
22
0
Order By: Relevance
“…These findings confirm the results reported by Cholitgul et al [46]. However, Eberhard et al [47] expressed opposition to these findings. Many studies have supported the idea that joint effusion, defined as a large collection of fluid in the articular space, is generally associated with TMJ pain and inflammatory responses [10,[48][49][50][51][52].…”
Section: Discussionsupporting
confidence: 89%
“…These findings confirm the results reported by Cholitgul et al [46]. However, Eberhard et al [47] expressed opposition to these findings. Many studies have supported the idea that joint effusion, defined as a large collection of fluid in the articular space, is generally associated with TMJ pain and inflammatory responses [10,[48][49][50][51][52].…”
Section: Discussionsupporting
confidence: 89%
“…Few studies described that the coronal plane of MR imaging is the ideal plane for assessment of the integrity of the congruency of the disc in the medial-lateral dimension and detection of sideway displacement [7][8][9][10]. In this work, coronal section of MR as transverse section at ultrasound in the opened mouth is the best plane for assessment of the sideway displacement.…”
Section: Discussionmentioning
confidence: 94%
“…Sideway displacement is commonly associated with variable degree of anterior disc displacement and it is therefore classified as either antero-medial or anterolateral displacement. Few studies have been discussing the value of MR imaging at coronal plane in diagnosis of sideway displacement of TMJ [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Third, evaluation of mediolateral disk position was qualitative. Eberhard et al (22) reported that quantitative evaluation of mediolateral disk position more accurately described the relationship between mediolateral disk position and other variables, including the angle of the LPM relative to the condyle. Additional studies, with larger numbers of participants, are needed in order investigate the complex pathologies of anterior and sideways disk displacement of the TMJ.…”
Section: Discussionmentioning
confidence: 99%